The Role of Lytic Infection for Lymphomagenesis of Human γ-Herpesviruses - Münz, Christian (Frontiers in Cellular and Infection Microbiology, 2021)
Epstein Barr virus (EBV) and Kaposi sarcoma associated herpesvirus (KSHV) are two oncogenic human γ-herpesviruses that are each associated with 1-2% of human tumors. They encode bona fide oncogenes that they express during latent infection to amplify their host cells and themselves within these. In contrast, lytic virus particle producing infection has been considered to destroy host cells and might be even induced to therapeutically eliminate EBV and KSHV associated tumors. However, it has become apparent in recent years that early lytic replication supports tumorigenesis by these two human oncogenic viruses. This review will discuss the evidence for this paradigm change and how lytic gene products might condition the microenvironment to facilitate EBV and KSHV associated tumorigenesis.